Self-efficacy and psychosocial risks in technical staff of an adoption service. - Sergio Sánchez-Sevilla; Rocío Guil Bozal; Serafín Cruces Montes; Antonio Zayas García (INFAD, 2017)
It is necessary that Psychology continues to devote efforts to map psychosocial risks in different occupations, as well as to facilitate the understanding of the relationship between risks and consequences, including the role of vulnerability and protective factors. This study brings as a novelty the evaluation of psychosocial risks in a group that has not been studied until now: the technical staff of a service of information, training, assessment of suitability and post-adoption follow-ups in international adoption procedures. The objectives of this research are: to determine the proportion of professionals exposed to psychosocial risk working conditions; to establish the level of self-efficacy of these professionals for working under conditions of psychosocial risk; to establish the relationship between the degree of exposure to psychosocial risks and the level of self-efficacy of these professionals. A cross-sectional study was carried out through a survey in which a sample of 51 technicians participated, out of a total of 72 people who composed the service in the Autonomous Community of Andalusia. The instruments used, in addition to a sociodemographic data form, were the Inventory of Psychosocial Risks (León Avargues, 2004) and the Professional Self-Efficacy under Psychosocial Risk Conditions Scale (Sánchez-Sevilla, Guillén León-Rubio, 2006). The results showed that almost half of the people evaluated are exposed to very stressful working conditions that are a risk to work life quality and health related to work stress. Regarding professional self-efficacy under psychosocial risk conditions, the sample as a whole had a moderate-high score. On the possible relationship of self-efficacy with the level of psychosocial risk borne by the professionals evaluated, an inverse relationship was found between both variables.